Cooperation in R&D and sample selection - Claudio Piga; Marco Vivarelli (Fondazione Eni Enrico Mattei (FEEM), 2002)
This study explicitly takes into account that the decision to enter into a cooperative R&D relationship is related to the antecedent decision to carry out R&D. This calls for a methodological approach that, at the same time, allows the joint analysis of the determinants of the two decisions and corrects for the sample selectivity that is intrinsic in the analysis of cooperative R&D. The results indicate the need to explicitly consider the selectivity issue in the empirical analysis of cooperative R&D. Moreover, the empirical evidence suggests that the role of the organizational form, the pursuit of multiple innovative objectives, the incentives to conduct R&D for those firms that are involved in close-knit vertical relationships are important drivers of a firm's decision to engage in R&D both independently and with external partners.
Keywords: L1; O3; 330; Cooperative R&D; bivariate probit; selectivity; outsourcing; business groups; Forschungskooperation; Industrielle Forschung; Entscheidung; Schätzung; Italien; Probit-Modell